2008
DOI: 10.1210/jc.2008-1001
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Markers Are Associated with Obesity in Nondiabetic Subjects

Abstract: Multiple markers of ER stress are activated in human adipose with obesity, particularly for protective chaperones downstream of activating transcription factor 6alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
178
5
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(199 citation statements)
references
References 35 publications
11
178
5
3
Order By: Relevance
“…32,33 Moreover, the intrinsic follicular dysplasia associated with the ovarian granulosa cell apoptosis was observed with significantly higher apoptotic rates in granulosa cells of patients with PCOS. It was suggested that endoplasmic reticulum stress might be involved in the pathogenesis of anovulation in patients with PCOS.…”
Section: Resultsmentioning
confidence: 98%
“…32,33 Moreover, the intrinsic follicular dysplasia associated with the ovarian granulosa cell apoptosis was observed with significantly higher apoptotic rates in granulosa cells of patients with PCOS. It was suggested that endoplasmic reticulum stress might be involved in the pathogenesis of anovulation in patients with PCOS.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, FGF21 appears to be a regulatory factor in the proteostasis network and not merely an end-point regulator in the negative feedback loop. ER stress is thought to be caused not only by accumulation of excess unfolded or misfolded proteins in the ER but also pathogenetic conditions, such as obesity and diabetes (23)(24)(25)(26)(27), and physiological conditions such as fasting and refeeding (18). In addition, treatment with chemical chaperones that reduce ER stress improved several metabolic parameters including insulin sensitivity (28).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a negative efect of excessive packing of fat by the adipocyte includes induction of cellular hypoxia through inhibition of efective oxygen supply from the circulation [46]. Another negative intracellular efect of adipocyte hypertrophy is a mechanical stress on the endoplasmic reticulum, condition that impairs protein folding [47]. Indeed, the adipocyte displays a potent inlammation as efect of the high storage of fat [48].…”
Section: Additional Considerations About Cell Biomechanics: the Casementioning
confidence: 99%